Regional Frequency Analysis With L-Moments For The Determination Of Drought Event Maps In High Andean Basins In Peru - Melania Zapana Quispe , Eduardo Chavarri-Velarde , Yénica Pachac Huerta , Robinson Peña Murillo , Yony Laqui Vilca , Waldo Lavado-Casimiro (Migration Letters, 2024)
Droughts are extreme climatic phenomena that are difficult to quantify spatially and temporally, due to the effects of climate change impacting socio-economic development. In this context, the research aims to estimate and map the frequency of theoretical meteorological droughts at different return periods through the method of regional frequency analysis (ARF) based on L-moments (LM), using 97 virtual stations from the gridded PISCO product based on annual mean precipitation (PMA). Two homogeneous rainfall regions were identified using a combination of the Ward method and the LM approach. For ARF, the generalized normal distribution (GNO) was selected due to its best fit with the ZDIST statistic, which allowed for the determination of the regional growth curve (quantiles). Finally, exponential predictive equations were obtained at a regional scale to relate LM and PMA, enabling the generation of meteorological drought maps.